Result of Open Reduction Kirschner Wire Fixation of Late Presentation of Lateral Condyle Fracture of Humerus in Children - Ma Nwet; Vignesh Ramachandran; Swe Swe Latt; Win Khaing; Soe San; Htet Aung Kyaw (Asian Journal of Medicine & Health Sciences, 2021)
Background: Management of lateral condyle fracture of the humerus needs accurate reduction and stabilization because of rotational displacement. Neglected lateral condyle fractures of humerus are misdiagnosed or insufficiently treated fractures, presenting later than 3 weeks after injury. This study aimed at analyzing the morphological and functional outcomes with hospital-based prospective and descriptive clinical study design of the neglected lateral condyle fracture of humerus in children at the Yangon Children Hospital, Myanmar. Methods: Sixty-two patients with unilateral neglected lateral condyle fractures of humerus were included in the study from January 2017 to January 2020. Seven patients had Milch’s type I fracture and 55 patients had Milch’s type II fractures. Open reduction with two smooth Kirschner wire fixation was done. Long arm plaster of Paris (POP) posterior slab was applied with the elbow at 90 degrees of flexion and forearm in a neutral position. Six weeks after the operation, the POP posterior slab and Kirschner wires were removed following a radiograph check. Thereafter, all patients were assessed both functionally and radiologically every month. Results: The outcome of 12 months follow up data were calculated. For the radiological union time, the age group of less than 5 years and 5 years of age group achieved the bone union considerably faster than the age of 6 to 10 years of age group and above 10 years of age group. (p<0.001). According to the Hardacre Scoring System for the Clinical Evaluation, 96.7% of the patients had good and excellent outcome scores using the data of 12-month follow-up. Hardacre score of an excellent and good result was statistically significantly different from the mean age of the fair functional results with p=0.018 and p=0.039. Conclusion: The study findings showed that open reduction and internal fixation in a majority of neglected lateral condyle fractures of the humerus in children gain good radiological and functional outcomes.